Mediation and governance in fragile contexts small steps to peace - Dekha Ibrahim Abdi 1964-2011; Mason, Simon A. 1971- (Kumarian Press, A divison of Lynne Rienner Publishers, Inc., 2019)
"Introduces an innovative, practical approach to resolving an enduring issue: How can conflicts be resolved in polarized societies and fragile states?"--
Keywords: Konfliktlösung; Friedenskonsolidierung; Kenia; Somalia; Conflict management / Africa, East; Mediation / Africa, East; Peace-building / Africa, East